How do foreign SMEs mitigate violent conflict risk by doing good?: an instrumental stakeholder theory perspective - Shou, Yongyi (Journal of business ethics, 2024)
Large foreign firms' interventions in violent conflicts have drawn increasing research attention. Nonetheless, scant research has investigated how foreign small and medium-sized enterprises (SMEs), which have little capacity in peacebuilding, can protect themselves from violent conflict risk. Drawing upon the instrumental stakeholder theory (IST), this study explores two specific local community-oriented corporate social responsibility (CSR) practices (i.e., corporate philanthropy and workforce localization) as violent conflict risk buffering strategies for foreign SMEs. Further, we examine their varying effects in different institutional environments (i.e., host country media freedom and labor rights protection). Using data from a cross-country survey of Chinese foreign SMEs combined with archival data from multiple sources, we empirically confirm the attenuating effects of both corporate philanthropy and workforce localization on foreign SMEs’ violent conflict risk. Besides, we discover that host country labor rights protection strengthens the mitigation impact of workforce localization on violent conflict risk. Our study advances the literature on IST and CSR by revealing the risk mitigation mechanism of CSR activities for foreign SMEs and elucidating its institutional boundary conditions.